The world through the eyes of the international news agencies: an analysis of photographs published in the world section of The Star and The New Straits Times / Noor Mayudia Mohd Mothar, Siti Hajar Abd Aziz and Shahril Anuar Abdul Ghalim - Mohd Mothar, Noor Mayudia; Abd Aziz, Siti Hajar; Abdul Ghalim, Shahril Anuar (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
The saying “one picture is worth a thousand words” demonstrates the importance of pictures or photographs and the information that they can convey. Written and spoken words are essential for communication, but photographs can make a point even more powerful. Newspapers trying to report news can make good use of photographs to show what is going on in the world. To some extent, photographs can be manipulated to send underlying messages and create perceptions among the readers. In view of this, a study was conducted for three consecutive months starting from February 2009 until April 2009 in the World Section to understand the messages behind the photographs published in the world section of two English mainstream newspapers, The Star and The New Straits Times. As most news and photographs in the World Section of both newspapers were provided by international news agency, the main objective of the study was to analyze and rate these photographs as positive, negative, or neutral. The study would identify which international news agency has its photographs published the most. The study too will look at the theme, size and frequency ofthe photographs featured in this section. From the study, the researchers hope to explain the use of photograph in the world section of two English mainstream newspapers